PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 008 PEMATANG SEMUT - Aisyah '; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research study IPS poor performance of students, with an average of 60.75. While the value of minimum completeness criteria (KKM) IPS is 70. Among the students who were 18 people, only 6 people reach KKM. This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPS fifth grade students of SD Negeri 034 Pematang Semut by implementing cooperative learning model Snowball throwing. The problems in this study is whether the implementation of cooperative learning model Snowball throwing can improve learning outcomes IPS fifth grade students of SD Negeri 034 Pematang Semut? The research was conducted from April to May 2016. From the data analysis activities of teachers percentage increases in the first cycle of the first meeting of 61.36%, the second meeting of the second cycle increased to 77.34%. While the percentage of student activity in the first cycle the first meeting 53.37% increase at every meeting, the second meeting of the second cycle increased to 75.00%. increased activity of teachers and students has been accompanied by increasing learning outcomes of a mean value of 59.28 into 79.76 with a percentage increase of 49.01% Thus, during the execution of the second cycle of this study indicate that the application of cooperative learning model Snowball throwing can improve learning outcomes IPS fifth grade students of SD Negeri 034 Pematang Semut.Key Words: Snowball throwing Cooperative mode, IPS Learning Outcomes